Introduction to Women, Gender, Sexuality Studies - Kang, Miliann; Lessard, Donovan; Heston, Laura; Nordmarken, Sonny; Open Textbook Library (Open Textbook Library, 2017)
This textbook introduces key feminist concepts and analytical frameworks used in the interdisciplinary Women, Gender, Sexualities field. It unpacks the social construction of knowledge and categories of difference, processes and structures of power and inequality, with a focus on gendered labor in the global economy, and the historical development of feminist social movements. The book emphasizes feminist sociological approaches to analyzing structures of power, drawing heavily from empirical feminist research.
Unit I: An Introduction to Women, Gender, Sexuality Studies: Grounding Theoretical Frameworks and Concepts -- Critical Introduction to the Field -- Theorizing Lived Experiences -- Identity Terms -- Conceptualizing Structures of Power -- Social Constructionism -- Intersectionality -- References: Unit I -- Unit II: Challenging Binary Systems and Constructions of Difference -- Introduction: Binary Systems -- The Sex/Gender/Sexuality System -- Gender and Sex - Transgender and Intersex -- Sexualities -- Masculinities -- Race -- Class -- Alternatives to Binary Systems -- References: Unit II -- Unit III: Institutions, Culture, and Structures -- Introduction: Institutions, Cultures, and Structures -- The Family -- Media -- Medicine, Health, and Reproductive Justice -- The State, Law, and the Prison System -- Intersecting Institutions Case Study: The Struggle to End Gendered Violence and Violence Against Women -- References: Unit III -- Unit IV: Gender and Work in the Global Economy -- Introduction: Gender and Work in the Global Economy -- Gender and Work in the US -- Gender and the US Welfare State -- Transnational Production and Globalization -- Racialized, Gendered, and Sexualized Labor in the Global Economy -- References: Unit IV -- Unit V: Historical and Contemporary Feminist Social Movements -- Introduction: Feminist Movements -- 19th Century Feminist Movements -- Early to Late 20th Century Feminist Movements -- Third Wave and Queer Feminist Movements -- References: Unit V
In English.
Description based on print resource
Keywords: Social sciences -- Textbooks; Gender and Sexuality Studies -- Textbooks; Economics -- Textbooks